Sustainability reporting as a tool for attracting investments for the green reconstruction of Ukraine's agibusiness - Volodymyr Metelytsia (2023)
Introduction. Global trends in the decarbonization of production and the development of the green economy prove that the principles of sustainable development have become a key reference point for making management decisions. Ukrainian agribusiness suffered huge losses due to military actions, so significant funds are needed for its reconstruction. To attract foreign investments, agricultural enterprises must prove their commitment to sustainable development goals by disclosing relevant information in the reporting. Purpose. The article aims to substantiate the practicality of preparing and publishing the Report on Sustainable Development as a tool for attracting investments for the green reconstruction of Ukraine's agricultural sector and to reveal its information content. Methods. The paper uses an abstract-logical method to substantiate the benefits of reporting on sustainable development by agricultural enterprises. Based on the application of methods of analysis and synthesis, induction and deduction, and logical generalization, the content (indicators) of the Report on Sustainable Development and Investments was revealed. Using the analogy method made it possible to strengthen the justification of the importance of sustainability reporting in Ukraine based on the EU countries' experience and the agribusiness need for foreign investments. Results. The paper systematizes the indicators of the Report on Sustainable Development and Investments in the agricultural sector and reveals some aspects of the normative regulation of sustainability reporting. An analysis of the factors of agricultural production was carried out, the disclosure of which in the Report on Sustainable Development will increase the agricultural enterprise's investment attractiveness and testify to its desire to be more open (accountable) to society. Conclusion. Sustainability reporting can be a tool for an agribusiness to better understand its impact on the environment and risks and manage them more effectively, successfully use new opportunities and solve specific challenges to become a leader in sustainable development. The Report on Sustainable Development and Investments in the agricultural sector ensures greater transparency of the enterprise's activities. It demonstrates to interested parties and the public its commitment to the principles of sustainable development, which increases the chances of successfully attracting external financing – foreign investments. – – , . , , . . , , , . , – .
Keywords: M41; Q01; Q14; Q15; Q51; 330; sustainability reporting; ESGI-report; evaluation of the enterprise's activity; foreign investments; green reconstruction of the economy; Ukraine's agribusiness; ESGI-; o